2014
DOI: 10.7314/apjcp.2014.15.6.2929
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Operative Evaluation of Ovarian Tumors by Risk of Malignancy Index, CA125 and Ultrasound

Abstract: Purpose: To evaluate the diagnostic performances of risk of malignancy index (RMI), CA-125 and ultrasound score in differentiating between benign and borderline or malignant ovarian tumors and find the best diagnostic test for referral of suspected malignant ovarian cases to gynaecologic oncologists. Materials and Methods: This prospective study covered 467 women with pelvic tumors scheduled for surgery at our hospital between July 2011 and July 2013. The RMI was obtained from ultrasound score, CA125 and menop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 18 publications
5
16
0
Order By: Relevance
“…In our study we found sensitivity 73.5%, specificity 97.1%, PPV 95.3% and NPV 82% by using RMI of more than 200. In the literature different values were defined for RMI and our results confirmed these studies (Jacobs et al, 1990;Davies et al, 1993;Tingulstad et al, 1999;Manjunath et al, 2001;Anderson et al, 2003;Ma et al, 2003;Obeidat et al, 2004;Yamamoto et al, 2009;Van der Akker et al, 2010;Ashrafgangooei et al, 2011;Van Gorp et al, 2012;Sayasneh et al, 2013;Terzic et al, 2013;Arun-Muthuvel et al, 2014).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our study we found sensitivity 73.5%, specificity 97.1%, PPV 95.3% and NPV 82% by using RMI of more than 200. In the literature different values were defined for RMI and our results confirmed these studies (Jacobs et al, 1990;Davies et al, 1993;Tingulstad et al, 1999;Manjunath et al, 2001;Anderson et al, 2003;Ma et al, 2003;Obeidat et al, 2004;Yamamoto et al, 2009;Van der Akker et al, 2010;Ashrafgangooei et al, 2011;Van Gorp et al, 2012;Sayasneh et al, 2013;Terzic et al, 2013;Arun-Muthuvel et al, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…Ovarian malignancy a common cause of adnexal mass is the most common second gynecological malignancy and the most lethal gynecologic cancer (Wanapirak et al, 2006;Arun-Muthuvel et al, 2014). In preoperative assessment prediction of the benign or malignant character of an adnexal mass is important and an accurate diagnosis is required for choosing appropriate management method.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, 4 malignant ovarian masses (80.0%) were in the age group above 45 years, while only 1 case (20%) was in age group less than 30 years. Our findings were similar to studies conducted by Jung Woo Park et al (8) and Veluswamy Arun Muthuvel et al (9) , wherein age group less than 45 years constituted the largest group and rate of malignant ovarian masses were highest in age group above 45 years. In the present study, youngest patient was 12 years old and oldest patient was 70 years old.…”
Section: Agesupporting
confidence: 92%
“…There is no established screening method for ovarian cancer; thus, 60-70% patients are at stage III or IV at the time of initial diagnosis (Arun-Muthuvel and Jaya, 2014). Currently the standard-of-care therapy for ovarian cancer is debulking surgery to minimize residual disease, followed by intravenous chemotherapy (IV CT) with a combination of a platinum analogue and paclitaxel (Chumworathayi, 2013;Koo et al, 2014;Suprasert et al, 2014).…”
Section: Introductionmentioning
confidence: 99%